EFEKTIVITAS METODE PETA PIKIRAN DALAM PEMBELAJARAN MENULIS TEKS BERITA SISWA KELAS VIII SMPN 1 WIDASARI - Juidah, Imas (Universitas Wiralodra, 2016)
This study aims to: (1) find out the activity of the teacher and eighth grade students of SMP Negeri 1 Widasari Indramayu in learning writing of news item text by using mind mapping, (2) know the ability profile of eighth grade students of SMP Negeri 1 Widasari in writing news item text before and after using mind mapping, (3) know the effectivity of mind mapping method toward writing news item text ability of the eighth grade students in SMP Negeri 1 Widasari. To achieve that goal, quasi-experimental research design with one group pretest-posttest is conducted. The results showed: (1) the teacher activity in learning writing of news item text by using mind mapping is in good categories with the score 82.5. Student activity in learning writing of news item text by using mind mapping is in good categories with the percentage of 53.33, (2) the students ability profile in learning writing of news item text before using the mind mapping is in sufficient category with an average score 65.2. While the profile of students ability in learning writing of news item text after using mind mapping is in good categories with an average score 83.53, (3) mind mapping method effective the ability to write news item text because tcount (3.233) is higher than ttable (1.701). Keywords: Learning, Method, Mind Mapping, Learning Achievement in Writing News Item Text